Simultaneous Polar and Cluster Observations in the Northern and Southern Middle‐Altitude Polar Cusps Around Equinox. Issue 12 (26th November 2020) - Pitout, F.; Marchaudon, A.; Trattner, K. J.; Berchem, J.; Laakso, H.; Escoubet, C. P.
Abstract: We present an event of simultaneous observations of the northern and southern middle‐altitude polar cusps by the Polar spacecraft and Cluster fleet that occurred on 23 September 2004. We examine the possible asymmetries in the fields and plasma parameters, although the proximity of the equinox should limit these asymmetries. Ion sensors reveal two dispersions in both cusps, and data analysis leads to the conclusion that those dispersions are due to pulsed reconnection at a single X‐line, which runs along the subsolar magnetopause. While the electromagnetic and particle energy fluxes injected in both cusp are globally very similar, we report significant differences in ion dispersions, width of the low‐latitude boundary layer, and peak convection velocities. We ascribe these differences to the dipole tilt that introduces an asymmetry in the magnetosheath flow at the exterior cusps. Key Points: Data from Cluster and Polar show a symmetry in ion injections in the magnetospheric cusps Signatures corresponding to a single reconnection line running along the subsolar magnetopause and pulsed reconnection are highlighted Differences in convection velocities are found and ascribed to the effect of the tilt angle